Kewenangan Pemerintah Pusat dan Daerah dalam Kerangka Green Tax Reform - Siti Rahma Novikasari (Jurnal Hukum IUS QUIA IUSTUM, 2023)
This research is aimed at examining the dynamics of the authority of the Central Government and Regional Governments as well as examining the expansion of authority that can be granted within the framework of green tax reform. This research uses juridical legal research methods with historical, conceptual, statutory, and comparative approaches. The results of the study concluded that the 3 (three) green tax reforms that have been implemented in Indonesia have strengthened several authorities, however, there are degraded authorities such as the authority to impose sanctions, resolve administrative disputes and budget authority. The authority of the central government and regional governments needs to be expanded and strengthened in the next green tax reform, specifically in the form of the authority to add potential types of environmental taxes in the regions, the authority for green budgeting, tax incentives/fiscal convenience, and the reorganization of the authority to grant administrative sanctions and resolve disputes administratively.Keywords: Authority; Environmental Tax; Government; Green Tax Reform AbstrakPenelitian ini ditujukan untuk mengkaji dinamika kewenangan Pemerintah Pusat dan Pemerintah Daerah serta menelaah perluasan kewenangan yang dapat diberikan dalam kerangka green tax reform. Penelitin ini menggunakan metode penelitian hukum yuridis dengan pendekatan historis, konseptual, pendekatan perundang-undangan, dan pendekatan komparatif. Hasil kajian menyimpulkan bahwa, 3 (tiga) green tax reform yang telah terlaksana di Indonesia memberikan penguatan pada beberapa kewenangan, meskipun demikian terdapat kewenangan yang terdegradari seperti kewenangan pemberian sanksi, penyelesaian sengketa administratif dan kewenangan anggaran. Kewenangan pemerintah pusat dan pemerintah daerah perlu diperluas dan diperkuat dalam green tax reform selanjutnya secara spesifik dalam bentuk kewenangan menambah jenis pajak lingkungan hidup yang potensial di daerah, kewenangan green budgeting, insentif perpajakan/kemudahan fiskal, dan pengaturan kembali kewenangan pemberian sanksi administrasi serta penyelesaian sengketa administratif. Kata-kata kunci: Kewenangan; Pajak Lingkungan Hidup; Pemerintah; Reformasi Pajak Hijau.